Alien futures: What is on the horizon for biological invasions?. Issue 8 (17th April 2018) - Dehnen‐Schmutz, Katharina; Boivin, Thomas; Essl, Franz; Groom, Quentin J.; Harrison, Laura; Touza, Julia M.; Bayliss, Helen
Abstract: Aim: To collect and identify the issues that may affect the future global and local management of biological invasions in the next 20–50 years and provide guidance for the prioritization of actions and policies responding to the management challenges of the future. Location: Global Methods: We used an open online survey to poll specialists and stakeholders from around the world as to their opinion on the three most important future issues both globally and at their respective local working level. Results: The 240 respondents identified 629 global issues that we categorized into topics. We summarized the highest rated topics into five broad thematic areas: (1) environmental change, particularly climate change, (2) the spread of species through trade, (3) public awareness, (4) the development of new technologies to enhance management and (5) the need to strengthen policies. The respondents also identified 596 issues at their respective local working levels. Management, early detection, prevention and funding‐related issues all ranked higher than at the global level. Our global audience of practitioners, policymakers and researchers also elicited topics not identified in horizon scanning exercises led by scientists including potential human health impacts, the need for better risk assessments and legislation, the role of human migration and water management. Main conclusions: The topic areas identified in this horizon scan provide guidance where future policy priorities for invasive alien species should be set. First, to reduce the magnitude and speed of environmental change and its impacts on biological invasions; second, to restrict the movement of potentially invasive alien species via trade; third, to raise awareness with the general public and empower them to act; and finally, to invest in innovative technologies that can detect and mitigate adverse impacts of introduced species.